2007
DOI: 10.1016/j.jadohealth.2006.11.147
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Physical Activity and Perceived Competence: Does Change in Activity Level Impact Self-Perception?

Abstract: Purpose-To determine whether change in physical activity level impacts adolescents' selfperceptions.Methods-Using questionnaire responses from the Growing Up Today Study (GUTS) in 1997 and 1999, we evaluated data from 5,260 girls and 3,410 boys. Physical activity changes were compared to changes in perceived competence in 3 domains (social, athletic, and scholastic) as well as in global self-worth. Analyses controlled for sibling clustering as well as for potential confounders, including body mass index, cigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 30 publications
4
61
0
13
Order By: Relevance
“…Os benefícios da prática de exercícios físicos são importantes quando se trata de qualidade de vida, prevenção de doenças, estética e manutenção da saúde, tanto física (CDC, 2008) quanto mental (STEIN et al, 2007). No entanto a aderência dos jovens às práticas de exercícios físicos tem preocupado pesquisadores de diversas áreas.…”
unclassified
“…Os benefícios da prática de exercícios físicos são importantes quando se trata de qualidade de vida, prevenção de doenças, estética e manutenção da saúde, tanto física (CDC, 2008) quanto mental (STEIN et al, 2007). No entanto a aderência dos jovens às práticas de exercícios físicos tem preocupado pesquisadores de diversas áreas.…”
unclassified
“…For these studies, the greater the social competence, the lower the BMI [24] [27]. Two studies have found that adolescents who have increased the frequency of physical activity also increased the level of social competence and reduced the BMI [16] [18] showing that actions directed to these aspects are useful together. The use of media was also associated with social competence and obesity: the more time the obese adolescents spend in front of the TV, the worse their level of social competence [22].…”
Section: Discussionmentioning
confidence: 99%
“…Health Sedentary lifestyle, social competence and obesity (n = 2). Adolescents above the weight that increase the frequency of physical activity also increase the level of social competence for self-perception and self-esteem [16] [18]. In spite of this, Laberge, Bush and Chagnon [16] found that obese adolescents that have increased the frequency of physical activity had no significant difference in social competence in general or in self-control.…”
Section: Relationships Between the Components Of Social Competence Anmentioning
confidence: 99%
“…The lack of association suggests that participation in a weight loss program confers benefits on selfconcept that are independent of the changes in weight, such as other perceived improvements to physical appearance or greater acceptance of physical appearance. Previous research has demonstrated a positive association between increases in physical activity and dimensions of self-concept, 20 suggesting that change in variables such as physical activity should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%